2017
DOI: 10.1186/s13256-017-1485-y
|View full text |Cite
|
Sign up to set email alerts
|

Chest compression-related fatal internal mammary artery injuries manifesting after venoarterial extracorporeal membrane oxygenation: a case series

Abstract: BackgroundCardiopulmonary resuscitation-related bleeding, especially internal mammary artery injuries, can become life-threatening complications after initiating venoarterial extracorporeal membrane oxygenation owing to the frequent involvement of concomitant anticoagulant treatment, antiplatelet treatment, targeted temperature management, and bleeding coagulopathy. We report the cases of five patients who experienced this complication and discuss their management.Case presentationWe retrospectively evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…This case demonstrated that rare case of IMA injury related to CPR without chest wall fractures. IMA injury after CPR can be a life-threatening complication as it results in severe hypovolemic shock, ongoing blood loss, and extrapleural hematoma [ 3 ]. The association between chest wall fractures and IMA injury after CPR has not been well investigated; however, most of previous clinical cases presenting IMA injury after CPR often occurred at the level of the middle IMA and include rib and sternum fractures, which are thought to injure the IMA directly [ 3 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case demonstrated that rare case of IMA injury related to CPR without chest wall fractures. IMA injury after CPR can be a life-threatening complication as it results in severe hypovolemic shock, ongoing blood loss, and extrapleural hematoma [ 3 ]. The association between chest wall fractures and IMA injury after CPR has not been well investigated; however, most of previous clinical cases presenting IMA injury after CPR often occurred at the level of the middle IMA and include rib and sternum fractures, which are thought to injure the IMA directly [ 3 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-quality cardiopulmonary resuscitation (CPR) is crucial for survival from cardiac arrest [ 1 ]; however, various chest compression-associated injuries are reported [ 2 ]. Although rare, internal mammary artery (IMA) injury after CPR can be fatal [ 3 ]. The precise mechanism of IMA injury has not been established, but a possible cause is fracture of the ribs or sternum, which often occurs after CPR.…”
Section: Introductionmentioning
confidence: 99%
“…今回我々は,胸骨圧迫による肝損傷がECMOにより顕在化した2症例を経験した。医学中央雑誌とPubMedでそれぞれ「胸骨圧迫,肝損傷」,「cardiopulmonary resuscitation, liver injury」で検索を行ったところ,心肺停止後,胸骨圧迫による肝損傷を来し,肝損傷の出血がECMOにより顕在化した症例は我々の症例を含めて9例存在した(Table 1)。出血の認知について,胸骨圧迫をされた心肺停止症例に自己心拍後の超音波検査もしくはCT検査が有効であるとする報告が存在する , 。症例1は蘇生後救急外来で行った超音波検査では腹腔内出血は認めず,蘇生後のCT検査で出血を確認した。一方,症例2は救急外来で腹部の検査は行っておらず,また冠動脈治療後のCT検査も行っておらず出血の認知が遅れた。Table 1の症例では,いずれも集中治療室入室後にHb値低下や腹部膨隆に気づき,それから腹腔内出血を認識している。胸骨圧迫の合併症としての肝損傷や腹腔内出血は知られており,注意喚起を促す論文も出ているものの出血の認知が遅れることは実際少なくないと考えられる。蘇生後の超音波検査とCT検査は早期の出血を認知することが可能であるが,とくに超音波検査はベッドサイドで迅速かつ繰り返し行えるという利点があり有用である。胸骨圧迫による肝損傷はまさに鈍的外傷であり,治療方針についてはCT所見や循環動態に応じて決定される。循環動態が不安定であれば開腹止血術を行う必要がある。循環動態が安定し,造影CTで血管外漏出像を認めれば血管造影検査やそれに引き続くTAEを行う。循環動態が安定し,かつ造影CT検査で血管外漏出像を認めなければ保存的治療を行う 。心肺停止蘇生後症例に合併する線溶亢進型DICは組織低灌流や虚血に伴い産生される内因性線溶物質が引き起こすと考えられており,心肺停止時間が長いほどその合併頻度は高くなる 。Table 1の9症例のうちECMO使用中の胸骨圧迫後肝損傷に対して保存的治療を行ったものは予後不良であり,保存的治療は困難である可能性がある , 。本症例はECPRが行われているため,蘇生後であり,かつ抗凝固薬を使用した状態であった。凝固異常を伴う患者や抗凝固薬を使用している患者の肝損傷では,早期の開腹止血術を念頭に置いた治療戦略が奏功する可能性があると報告されている 。そのためECPR後の肝損傷では通常の肝損傷の対応よりも早期に開腹止血術を考慮すべきである。本症例2は早期にECMO離脱をすることができ,ECMO使用中に行ったCT検査の結果では明らかな血管外漏出像を認めずTAEの適応がないと判断した。しかし,結果として輸血療法でも循環動態が安定せず緊急開腹術を施行した。ECMO使用中の胸骨圧迫後肝損傷で出血が疑われる場合には,血管造影やそれに引き続く塞栓術などの止血処置を迅速に行うべきとされている 。また造影CT,血管造影検査で血管外漏出像を認めない場合でも支配動脈に対するTAEは有効であるという報告がある 。蘇生後の患者はカテコラミンの影響で血管が収縮しており損傷部位からの出血がわかりにくいケースもあるため,腹腔内出血が疑われる場合には止血処置をためらわないことが重要である 。ECMO使用中は回路閉塞を防ぐためにヘパリン持続投与が行われるが,ECMO使用中の患者では14~63%と高率に出血性合併症を生じるとされる 。その対応としては,まず新鮮凍結血漿や血小板輸血などによる凝固異常の補正である。次にヘパリンの減量,中止を行う。それでも出血コントロールが困難であればTAEや外科的止血術を行う 。本症例1では輸血療法とECMOの離脱で対応可能だったが,症例2では輸血療法やECMO離脱を行っても血圧の維持が難しく外科的止血術を行った。近年では,ECMO使用中のヘパリン投与については初期にヘパリンを使用せずECMOを行った報告もあり,本症例のように胸骨圧迫による外傷が懸念された症例については,当初ヘパリンを開始せず経過をみることは必要なのかもしれない 。また2症例目については,急性心筋梗塞に対して緊急の血管造影・経皮的ステント留置術が行われるとともに抗血小板剤の投与が出血の顕在化に関与した可能性があった。しかしKurkciyanらは,心筋梗塞により心肺停止となり胸骨圧迫を受けた症例で,血栓溶解薬や抗血小板薬を投与しても出血のリスクは有意に上昇しないとしている 。…”
Section: 考  察unclassified
“…2 Surgical thoracotomy and arterial embolization continue to offer life-saving options for achieving hemostasis in patients with active mediastinal hemorrhage. [5][6][7] We present a unique case of bilateral IMA laceration after CPR in a patient who presented with ST-segment elevation myocardial infarction. with an active hemorrhage secondary to trauma received from CPRassociated chest compressions.…”
Section: Introductionmentioning
confidence: 99%
“…Prompt diagnosis and treatment of CPR‐associated IMA injury is critical for preventing anterior mediastinal hemorrhage and progression to hypovolemic shock in these individuals . Surgical thoracotomy and arterial embolization continue to offer life‐saving options for achieving hemostasis in patients with active mediastinal hemorrhage . We present a unique case of bilateral IMA laceration after CPR in a patient who presented with ST‐segment elevation myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%